From Banking Model to Critical Pedagogy Challenges and Constraints in the University Classrooms - Sadia Kalsoom; Nazia Kalsoom; Rafia Javaid Mallick (University of Management and Technology, 2020)
Critical pedagogy, contrary to the banking concept of education, seeks to empower learners to think critically to transform their living conditions. This mixed-methods case study aims at exploring the actual teaching practices of the university teachers in order to demystify the challenges and constraints impeding the implementation of critical pedagogy in the universities of Punjab, Pakistan. Women University in Multan was the selected case and exploratory sequential design the method selected for this study. The researchers personally collected data using a small-scale survey with 100 students using cluster sampling, and in-depth interviews with ten teachers purposively selected from various departments of the university, ensuring equal representation. The study concluded that large class size, lack of needed resources and trained personnel, lengthy and fixed syllabus, and lack of student interest and motivation were the reasons for continuing with the 'banking method.' Based on the findings, the researchers recommend that for the critical pedagogy to take root in Pakistan, the teachers and students should be cognizant of the utility of critical pedagogy, and adequate resources must supplant the teaching and learning environment to enjoy best outcomes